Dairy in Adulthood: From Foods to Nutrient Interactions on Bone and Skeletal Muscle Health - Bonjour, Jean-Philippe; Kraenzlin, Marius; Levasseur, Régis; Warren, Michelle; Whiting, Susan (Journal of the American College of Nutrition, 2013)
The risk of fragility fractures exponentially increases with aging. Reduced mass and strength of both bone in osteoporosis and skeletal muscle in sarcopenia play a key role in the age-related incidence of fragility fractures. Undernutrition is often observed in the elderly, particularly in those subjects experiencing osteoporotic fractures, more likely as a cause than a consequence. Calcium (Ca), inorganic phosphate (Pi), vitamin D, and protein are nutrients that impact bone and skeletal muscle integrity. Deficiency in the supply of these nutrients increases with aging. Dairy foods are rich in Ca, Pi, and proteins and in many countries are fortified with vitamin D. Dairy foods are important souces of these nutrients and go a long way to meeting the recommendations, which increase with aging. This review emphaszes the interactions between these 4 nutrients, which, along with physical activity, act through cellular and physiological pathways favoring the maintenance of both bone and skeletal muscle structure and function.